Obtención de bioetanol a partir de residuos lignocelulósicos (2017)
Research has shown that residues of fruits, leaves and stems of plants have been treated as lignocellulosic material, in addition to starches, among others, in order to produce a renewable fuel. Theses residues were pretreated to separate the lignin and from the cellulose and, reducing sugars were obtained by means of a hydrolysis which may be acid, basic or enzymatic. Later the sugars are taken to a process of fermentation with strains of yeasts, which are in charge of transforming the sugars in bioetanol. At present, lignocellulosic biomass is an important substrate that is still being evaluated to increase the production of bioethanol; the highest amount of bioethanol obtained was 200 mL/kg of orange peels.